(untitled) (Revista "Boletín el Conuco", 2021)
work that contains the theoretical, conceptual, legal, institution and state of the art framework that are constituted as a structure for the development of the research Project, which aims to identify convergent actions to potentiate the agricultural and agroindustrial sector of the Meta Departament, through the commodities market. In relation to the abovem it is relevant to deepen the existing theories, regulations, policies and programs, since they provide guidance, conceptualizatioin, reference search, wich would lead to designing strategies to improve the access of agricultural and agroindustrial producers to the Stock Exchange Mercatile of Colombia and increase the use of its productive potential. The result of the construction of the referential framework provides the analysis and interpretation of current theories, laws, norms and policies as support for the socpe of the proposed objectives and the methodological development of the research.